2010
DOI: 10.1245/s10434-010-1138-5
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of PFDN4 in Colorectal Cancer: A Novel Marker for Prognosis

Abstract: The data strongly suggest that PFDN4 expression is a prognostic factor in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…In vitro experiments have shown that PFDN4 plays an important role in tumor cell growth, invasiveness, and metastasis [44,45]. However, the role of PFDN4 in cancer progression is unclear because colorectal cancer patients with high tumor PFDN4 expression have been reported to have a better prognosis [45], whereas in the present study HCC patients with gain of 20q13.12-13.33 where PFDN4 located had a worse prognosis and high PFDN4 expression was associated with tumor vascular invasion. The genes ZNF64 and DDX27 have been found upregulated as a consequence of 20q gain in cervical cancer [46], but their functions in cancer development are not well understood.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In vitro experiments have shown that PFDN4 plays an important role in tumor cell growth, invasiveness, and metastasis [44,45]. However, the role of PFDN4 in cancer progression is unclear because colorectal cancer patients with high tumor PFDN4 expression have been reported to have a better prognosis [45], whereas in the present study HCC patients with gain of 20q13.12-13.33 where PFDN4 located had a worse prognosis and high PFDN4 expression was associated with tumor vascular invasion. The genes ZNF64 and DDX27 have been found upregulated as a consequence of 20q gain in cervical cancer [46], but their functions in cancer development are not well understood.…”
Section: Discussionmentioning
confidence: 47%
“…PFDN4, a transcriptional factor that regulates cell cycle, is highly expressed in breast cancer cell lines and tumor tissues and has been reported as a candidate tumor-related gene [42,43]. In vitro experiments have shown that PFDN4 plays an important role in tumor cell growth, invasiveness, and metastasis [44,45]. However, the role of PFDN4 in cancer progression is unclear because colorectal cancer patients with high tumor PFDN4 expression have been reported to have a better prognosis [45], whereas in the present study HCC patients with gain of 20q13.12-13.33 where PFDN4 located had a worse prognosis and high PFDN4 expression was associated with tumor vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that chaperones are found at increased levels in many solid tumours and haematological malignancies [5], [6]. Their expression may in part account for the ability of malignant cells to maintain protein homeostasis in the unfavourable hypoxic and acidic microenvironment of the tumour.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the prefoldin subunit may function independently. PFD4 expression is a prognostic factor in breast and colorectal tumor and cancer cells [22]. PFD2 was identified as a biomarker of bladder cancer cells [23].…”
Section: Discussionmentioning
confidence: 99%